2021
DOI: 10.3390/nu13072470
|View full text |Cite
|
Sign up to set email alerts
|

Both Isocarbohydrate and Hypercarbohydrate Fruit Preloads Curbed Postprandial Glycemic Excursion in Healthy Subjects

Abstract: This study aimed to investigate the impact of fruit preloads on the acute postprandial glycemic response (PGR) and satiety response of a rice meal in healthy female subjects based on iso-carbohydrate (IC) and hyper-carbohydrate (HC) contents, respectively. The IC test meals including (1) rice preload (R + 35R), (2) orange preload (O + 35R), (3) apple preload (A + 35R) and (4) pear preload (P + 35R), contained 50.0 g available carbohydrates (AC) where the preload contributed 15.0 g and rice provided 35.0 g. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Snacks are generally recommended to be under 200 kcal for adults [ 23 ]. In this study, 70 kcal was set as the energy intake of the snacks based on our previous study, which found that an apple preload of 70 kcal could remarkably improve the blood glucose stability at the subsequent meal [ 9 ]. In order to eliminate the differences in energy intake between the snack groups and the control group, the lunch energy of the non-snack control was 70 kcal higher than that of the snack groups, but with exactly the same macronutrient composition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Snacks are generally recommended to be under 200 kcal for adults [ 23 ]. In this study, 70 kcal was set as the energy intake of the snacks based on our previous study, which found that an apple preload of 70 kcal could remarkably improve the blood glucose stability at the subsequent meal [ 9 ]. In order to eliminate the differences in energy intake between the snack groups and the control group, the lunch energy of the non-snack control was 70 kcal higher than that of the snack groups, but with exactly the same macronutrient composition.…”
Section: Discussionmentioning
confidence: 99%
“…Fruits and nuts are recommended to be included in the daily diet in many countries [ 24 ], as the consumption of fruit and nuts is proven to be inversely associated with the risk of certain cancers, diabetes, and cardio-metabolic diseases [ 25 , 26 , 27 , 28 , 29 , 30 ]. As a glycemic-friendly food, apple is not only a low-GI food, but can also effectively mitigate the postprandial glycemic response when ingested as a preload food [ 9 ]. Moreover, apple is available across seasons and throughout the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, components of kiwifruit, apart from sugars, add to the anti-glycaemic effect [ 6 ]. The combination of kiwifruit sugars and properties of digested kiwifruit remnants in the gut may cause a substantial lowering of glycaemic response to a co-consumed starchy cereal [ 3 ], an effect that has been noted in other fruit [ 7 ].…”
Section: Introductionmentioning
confidence: 99%